A new myrmecophilous genus of Falagriini from Colorado, USA (Coleoptera: Staphylinidae: Aleocharinae) - Eldredge, K. Taro (Zootaxa, 2022)
A new genus and species, Myrmecoagria hoebekei is described as the first known myrmecophilous representative of Falagriini in North America. The new species is believed to be associated with Myrmica ants based on an associated host specimen and label data. Ahn & Ashe’s (1995) dataset is modified to investigate the placement of Myrmecoagria and evolution of myrmecophily within Falagriini. Sceptobiini, a long suspected close relative of Falagriini was included in the analysis and was recovered nested within Falagriini. Myrmecoagria was recovered distant to Myrmecopora, a genus with anatomical similarities.